Помогитеупростить выражение

Помогитеупростить выражение
Гость
Ответ(ы) на вопрос:
Гость
[latex] \frac{m^{2}-6m+9 }{m^{5} n} : \frac{m^{2} -3m}{mn^{4} }= \frac{(m-3)(m-3)}{m^{5}n }* \frac{mn^{4} }{m(m-3)}= \frac{n^{3}(m-3)}{m^{5} } [/latex] / [latex]( \frac{y-1}{y+1} - \frac{y+1}{y-1})*( \frac{1}{2}- \frac{y}{4}- \frac{1}{4y})=( \frac{(y-1)(y-1)-(y+1)(y+1)}{(y-1)(y+1)})( \frac{2y-y^{2} -1}{4y})= [/latex][latex] \frac{y^{2}-2y+1-y^{2}-2y-1}{(y-1)(y+1)}* \frac{(y-1)(y-1)}{4y} =- \frac{4y}{y+1} * \frac{y-1}{4y}=- \frac{y-1}{y+1} [/latex]
Не нашли ответ?
Ответить на вопрос
Похожие вопросы